Small antenna handbook - Hansen, Robert C.; Collin, Robert E. (Oxford, United Kingdom : Wiley-Blackwell, 2011)
Now in an completely revised, updated, and enlarged Second Edition, Small Antennas in Portable Devices reviews recent significant theoretical and practical developments in the electrically small antenna area.
Includes bibliographical references.
Keywords: ANTENNAS (ELECTRONICS)